2023
DOI: 10.3389/fvets.2023.1095293
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of patterns of livestock movements in the Cattle Corridor of Uganda for risk-based surveillance of infectious diseases

Abstract: IntroductionThe knowledge of animal movements is key to formulating strategic animal disease control policies and carrying out targeted surveillance. This study describes the characteristics of district-level cattle, small ruminant, and pig trade networks in the Cattle Corridor of Uganda between 2019 and 2021.MethodologyThe data for the study was extracted from 7,043 animal movement permits (AMPs) obtained from the Ministry of Agriculture, Animal Industry and Fisheries (MAAIF) of Uganda. Most of the data was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For example only 3/184 farms reported history of animal movements. The tracking of animal movements in Uganda is not well established and synchronized (González-Gordon et al, 2023; Hasahya et al, 2023; Payne et al, 2021). For example, the available animal movement tracking efforts are for those to be transported on major/highway roads and the motivation is trade and revenue generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example only 3/184 farms reported history of animal movements. The tracking of animal movements in Uganda is not well established and synchronized (González-Gordon et al, 2023; Hasahya et al, 2023; Payne et al, 2021). For example, the available animal movement tracking efforts are for those to be transported on major/highway roads and the motivation is trade and revenue generation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was motivated by Budasha et al and de Glanville, W. A. et al’s observation that RVF antibodies could be detected in abortions and their recommendation that these could be used as an early warning signal for RVF in endemic areas (de Glanville et al, 2022; Glanville et al, 2022). In Uganda and many African countries where animal health surveillance is not systematic (Hasahya et al, 2023; Qiu et al, 2023) livestock abortions are neither routinely documented nor reported for action, yet could be leveraged as cost-effective proxies for arboviruses surveillance in ruminants (Walt et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The network analysis presented here offers insight into the structure of cattle mobility in Uganda. By analysing the temporal patterns of country-wide cattle shipments for the purpose of trade and slaughter, we have extended the scope of the analyses by Mugezi et al and Hasahya et al 34 , 77 . These analyses focused on qualitatively assessing the risk of FMD during the dry season through pastoral and trade-related cattle mobility along the Ugandan-Tanzanian border and on studying the patterns of live trade livestock movements (cattle, small ruminants, and pigs) in the cattle corridor of Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to comprehensively characterise the network structure of cattle movements in Uganda based on official data collected in 2019. We considered this data to be an unaltered, representative overview of cattle movements before COVID-19 disrupted routine trading operations, distorting the collection of mobility data to date 33 , 34 . First, the annual static network is analysed as a snapshot of the cattle movements.…”
Section: Introductionmentioning
confidence: 99%